Student engagement as a predictor of effective higher educational practices. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2008)
The quest for excellence in teaching and learning in higher education is a world- wide concern. Universities and colleges have responded to the challenge for higher quality in instruction by looking closely at the nature of the teaching and learning environment.